Updating the content of education through the integration of seven modules - Ali, R (2021)
The article is devoted to the analysis of modern trends in the field of updating the content of school education of the Republic of Kazakhstan. The introduction of seven educational modules in the content of education will improve the quality of Kazakhstan's education. Finding ways to integrate the seven modules of education makes the study relevant. The author describes the educational modules and their impact on the content of education, focusing on ways to integrate seven modules in a single lesson, changing the content of education under the influence of educational modules.